The role of virulent Helicobacter pylori strains in the etiopathogenesis of coronary artery disease - Hakan YÜCEYAR; Murat Saruç; Şerife ARSLAN; Gamze GÖKSEL; Beril ÖZBAKKALOĞLU; Bekir Sami UYANIK; Ramazan YİĞİTOĞLU and Ahmet Zeki ŞENGİL (Turkish Journal of Gastroenterology, 2019)
-